ANALYSIS OF THE PROBLEMS OF TRANSLATION FROM WORLD LITERATURE INTO THE UZBEK LANGUAGE - Parvina A. Turgunboyeva; Diana Komilovna Ruzmetova (Modern American Journals, 2025)
This article analyzes the problems that arise in the process of translating world literature into Uzbek. Factors such as the artistic expression of the translation, cultural context, semantic differences, and changes in language structures are studied. Suggestions are made for improving the translation and the significance of the results for literary communication is emphasized.
Keywords: Translation, world literature, translation into Uzbek, artistic expression, culture, semantics, language structures, literary studies.